Ice sheet instability and meltwater events along the Svalbard–Barents Sea margin during the last 60,000 years - R.G. Lucchi; C. Caricchi; L. Sagnotti; M.E. Musco; G. Giorgetti; R. Ventrice; N. Douss; F. Princivalle; C. Morigi; P. Macrì; F.S. Gois Smith; A. Caburlotto; et al. (Global and Planetary Change, 2026)

Decoding Past Microbial Communities Shifts Induced by Natural and Anthropogenic Disturbance Events Through Extracellular DNA - S. Varrella; M. Tangherlini; C. Corinaldesi; L. Musco; A. Schirone; G. Armiento; R. Danovaro; A. Dell'Anno (Molecular Ecology, 2025)
Coastal marine ecosystems face escalating threats from multiple anthropogenic stressors, including the release of industrial contaminants. Despite decades of industrial activity impacting marine ecosystems, long‐term effects on microbial communities and related key ecological functions remain unclear. Here, we analysed the prokaryotic genetic signatures of extracellular DNA preserved in sediment layers dating from the mid‐17th century to the present day collected from two sites of one of the most polluted European coastal areas (i.e., Bagnoli‐Coroglio Bay, Tyrrhenian Sea), where industrial activities began in the early 20th century and ended in 1992. Archaeal 16S rDNA copy numbers were higher than bacterial ones, reaching values of 2.3 and 8.8 × 10 7 copies during pre‐industrial volcanic episodes and the intense industrial development period, respectively. Most of the archaeal genetic signatures identified along the sediment vertical profiles belong to Bathyarchaeia. The pre‐industrial period showed lower diversity in terms of Amplicon Sequence Variants (ASVs) belonging to 70 prokaryotic families when compared with industrialisation periods (182 families), suggesting prokaryotic ability to respond and change in relation to modified environmental conditions occurring over time. High microbial β‐diversity values were observed, with major shifts occurring for more than 50 prokaryotic taxa in both cores, suggesting that chemical contamination and volcanic eruptions fostered microbial succession, selecting certain taxa more adapted to cope with such adverse ecological conditions. Our findings indicate that extracellular DNA pools of marine sediments can hold information on long‐term changes in benthic microbial diversity, representing valuable archives for understanding ecosystem dynamics over time.

A revised inventory of Annelida in the Lebanese coastal waters with ten new aliens for the Mediterranean Sea - ANDREA TOSO; MATTEO PUTIGNANO; LARA M. FUMAROLA; MICHEL BARICHE; ADRIANA GIANGRANDE; LUIGI MUSCO; STEFANO PIRAINO; JOACHIM LANGENECK (Mediterranean Marine Science, 2024)
Sampling activities conducted in the Tyre Coast Nature Reserve, southern Lebanon, to study the marine annelid fauna of the area, allowed for the revision of the diversity of this group in Lebanon. We particularly focused on non-indigenous species (NIS), which were characterised from morphological and molecular points of view. A total of 116 taxa were collected; 10 species are reported here for the first time in the Mediterranean Sea, while 6 species with presumable Indo-Pacific affinity are likely new to science. Seventy-three taxa were native, while 43 taxa were NIS; among the latter, 24 species are reported for the first time in Lebanon. Molecular data were obtained for 28 NIS, representing the first data from the Mediterranean Sea for 23 of them. Non-indigenous annelids occurring along the coast of Lebanon mainly have Indo-Pacific affinity. However, molecular data highlighted inconsistencies between the sampled material and the sequences available in public repositories, suggesting the widespread occurrence of species complexes in these taxa. These results suggest that further research on Indo-Pacific annelids is needed to understand their diversity patterns and invasion pathways. Additionally, the large number of new records of annelids in Lebanese waters indicate that further studies are needed to explore their diversity in comparison with neighbouring Mediterranean regions.

Climate change adaptation mainstreaming through strategic environmental assessments. An in-depth analysis of environmental indicators from spatial plans in Friuli Venezia Giulia Region (Italy) - M. Granceri Bradaschia; D. Longato; D. Maragno; F. Musco (Environmental Impact Assessment Review, 2024)

I n vitro and in vivo studies of Cucurbita pepo L. flowers: chemical profile and bioactivity - Valeria M. Morittu; Nadia Musco; Vincenzo Mastellone; Marco Bonesi; Domenico Britti; Federico Infascelli; Monica R. Loizzo; Rosa Tundis; Vincenzo Sicari; Raffaella Tudisco; Pietro Lombardi (Natural Product Research, 2021)

Anchovy (Engraulis encrasicolus) early life stages in the Central Mediterranean Sea: connectivity issues emerging among adjacent sub-areas across the Strait of Sicily - B. Patti; R. Zarrad; O. Jarboui; A. Cuttitta; G. Basilone; S. Aronica; F. Placenti; G. Tranchida; G. M. Armeri; G. Buffa; R. Ferreri; S. Genovese; et al. (Hydrobiologia, 2018)

DNA barcoding and COI sequence variation in Mediterranean lanternfishes larvae - A. M. Pappalardo; A. Cuttitta; A. Sardella; M. Musco; T. Maggio; B. Patti; S. Mazzola; V. Ferrito (Hydrobiologia, 2015)

Distribution patterns of shallow water polychaetes (Annelida) along the Alexandria coast, Egypt (eastern Mediterranean) - M. M. DORGHAM; R. HAMDY; H. H. EL RASHIDY; M. M. ATTA; L. MUSCO (Mediterranean Marine Science, 2014)
Shallow hard bottom and intertidal soft bottom polychaete assemblages of the Alexandria coast, southeastern Mediterranean (Levantine Sea), were studied during a complete annual cycle in order to analyze spatial temporal patterns of variation in assemblages, and relevant factors related to polychaete distribution. The present study recorded a total of 73 species, belonging to Syllidae (22 species), Nereididae (9 species), Serpulidae (6 species), Eunicidae (5 species) and other 19 families. The assemblages experienced pronounced spatial and temporal variation throughout the study area, but spatial variation appeared more important in determining the observed patterns. Polychaete distribution related to variation of grain size and sessile macrobenthos cover suggesting that these structural variables accounted more than the physical-chemical ones (namely BOD, dissolved oxygen, organic carbon, organic matter, salinity, temperature, pH) in influencing the patterns of assemblages’ distribution. The present study is the southeastern-most one dealing with ecology and distribution patterns of hard bottom polychaetes from the Mediterranean Sea, as well as one of the few studies dealing with intertidal soft bottom polychaetes in the Levant Basin.

Shift in Sabella spallanzanii (Polychaeta, Sabellidae) spawning period in the Central Mediterranean Sea: a consequence of climate change? - A. GIANGRANDE; M. LICCIANO; L. MUSCO; L. STABILI (Mediterranean Marine Science, 2010)
Sabella spallanzanii is a large tubicolous filter feeder polychaete common in the Mediterranean fouling assemblages where it plays an important role in structuring the community. Its reproductive biology is well known and had been investigated since 1993. During the past few years a shift in its reproductive period has been observed. In 2008 the presence of ripe eggs in the females was observed at least two months in advance compared to the past. This was confirmed during the 2009 when spawning and fertilization were observed three months in advance compared to the past. Possible causes of this shift may be related to the increasing surface temperature in the Central Mediterranean Sea.

Reproduction activity of Exogone naidina (Polychaeta: Exogoninae) in a population from the Apulian coast (Adriatic Sea) - M. Gherardi; M. Mastrodonato; L. Sion; L. Musco; E. Lepore; M. Sciscioli; A. Giangrande (Marine Biology, 2005)

Polychaete assemblages along a rocky shore on the South Adriatic coast (Mediterranean Sea): patterns of spatial distribution - A. Giangrande; A. L. Delos; S. Fraschetti; L. Musco; M. Licciano; A. Terlizzi (Marine Biology, 2003)